The Influence of Internal Control System and Accountability of Village Fund Allocation Management on Village Financial Performance - Priantono, Seger; Vidiyastutik, Elok Dwi (International Journal of Social Science and Business, 2022)
In the process of managing the allocation of village funds that are good and correct it is expected to improve the quality of the village's financial performance. The weak management of village funds appears to be systematic which is confirmed by the results of a review of a number of evaluation studies of government institutions and Non-Governmental Organizations (NGOs). Accountability of village fund management as a form of accountability for village funds that have been entrusted as the implementation of the obligations of the village head in order to achieve village goals. Accountability is expected to be able to improve the quality of village government so that village fund management becomes a benchmark for community trust This research aims to test the influence of internal control and accountability systems simultaneously and partially on the financial performance of the village. The type of research used is quantitative research with a causal associative approach. The subjects of the study were all parties directly involved in the management of village funds allocation in Gending District of Probolinggo Regency amounted to 41 people. This type of data in the form of primary data is obtained through questionnaires and analyzed using multiple regression analysis. The results showed that the internal control and accountability system simultaneously had a significant effect on the financial performance of the village and the internal control system and partial accountability also had a significant effect on the financial performance of the village in the Gending Subdistrict of Probolinggo Regency. Internal control is required to provide and present financial statements in accordance with the laws and regulations on a regular basis, the prevailing regularity will provide effectiveness to financial performance as a mirror of the success that has been done by employees.